Inbreeding depression, reproductive trends, and biological variation in two interrelated Jumellea species with differing dispersal trends and commonness - Hassan, Abdullah Othman; Rashid, Rzgar Farooq; Abdulaqadir, Shang Ziyad; Hassan, Rawaz Rizgar (International journal of Rural Development, Environment and Health Research, 2021)
Genetic diversity and inbreeding can affect the long-term viability of plant populations subjected to size reductions, according to theory. In addition, a variety of life-history and ecological features can influence the response to population size reductions in different species. For the uncommon and fragmented Jumellea fragrans and its widely distributed congener, J. rossii, the reproductive patterns, levels of genetic diversity and degree of inbreeding depression were examined. Over-collection and fragmentation on J. fragrans were the primary goals of this study; we also wanted to learn more about their biology and ecology in order to better understand their medicinal and aromatic characteristics. For the purposes of determining the breeding system and assessing inbreeding depression, hand pollination experiments were done. Selfing rates and levels of genetic diversity were studied using nuclear microsatellite markers. During the germination stage (d 14 066) of Jumellea rossii, a mixed-mating system and evidence of inbreeding depression were discovered. Allele richness (AR) was 8 575 and expected heterozygosity (He) was 0 673. The genetic diversity was relatively high. Selfing rates in J. fragrans reflect an outcrossing mating mechanism. It is likely that the low levels of genetic diversity observed in this population were due to the outcrossing mating system and the comparatively high density of individuals compared to those found in J. rossii (AR 14 4983 and He 14 0492). According to researchers, Jumellea fra-grans did not display signs of inbreeding depression. Even if the long-term viability of the J. fragrans population is not in jeopardy, fragmentation and over-collection have likely diminished its genetic diversity. Both in situ and ex situ conservation measures for J. fragrans are proposed in order to meet local demand.